Moderasi Beragama Mahasiswa di Era Digital: Studi pada Kehidupan Kampus dan Ruang Media Sosial - Muh. Asyam Samjas (Lembaga Yasin AlSys, 2026)
This study is motivated by the limited empirical research that simultaneously examines students’ religious moderation in campus life and social media spaces, although both play an important role in shaping students’ religious attitudes in the digital era. This study aims to describe the level of students’ religious moderation, identify their patterns of attitudes toward religious issues in the digital era, and analyze the role of project-based learning in internalizing moderation values aligned with Islam wasathiyah. This study used a mixed methods design. Quantitative data were collected through a five-point Likert-scale questionnaire with 16 statement items involving 47 students across study programs at Universitas Negeri Makassar, while qualitative data were obtained through in-depth interviews with informants selected purposively. Quantitative data were analyzed descriptively, while qualitative data were analyzed using thematic analysis. The results show that students’ level of religious moderation was in the very high category, with an overall mean of 4.62 on a 1–5 scale and a Cronbach’s alpha coefficient of 0.95. The highest scores were found in the aspects of respect for differences in belief, rejection of violence in the name of religion, and comfort in interreligious relations. However, the aspects of verifying religious information and resilience against digital provocation still need to be strengthened. Interview data confirmed that social media is ambivalent because it can open spaces for dialogue while also serving as a medium for the spread of hoaxes and identity polarization. The conclusion of this study emphasizes that students’ religious moderation is already strong at the normative level and in direct social relations, but still requires strengthening in the dimension of religious digital literacy. The implications of this study include theoretical contributions to the development of Islamic Religious Education literature through the integration of wasathiyah values with digital literacy competencies, as well as practical contributions for educators in designing project-based Islamic Religious Education learning that explicitly integrates indicators of moderation and religious digital literacy as foundational competencies for students who are religious, moderate, and socially responsible.